The Effectiveness of Local Culture-Based Human Values in Efforts to Strengthen Pancasila Student Profiles in Elementary Schools - Astawaa, Dewa Nyoman Wija; Handayani, Ni Nyoman Lisna; Meylani, Vita (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Introduction: Human values, including Truth, Virtue, Peace, Compassion, and Non-Violence, should be ingrained and educated in pupils from a young age to enhance their character in accordance with a nation's standards. The degradation of human values can be attributed to the growing prevalence of individualist views that are in line with contemporary societal norms. It is imperative to enhance and cultivate human values that are rooted in indigenous knowledge and are congruent with the characteristics of Pancasila students. The objective of this study is to conduct a detailed analysis of various methodologies employed in the integration of human values into the development of Pancasila student profiles. Method: A qualitative research design and descriptive approach are employed in this study. The study was carried out in a State Elementary School located in the West Selemadeg District of Tabanan Regency. The data was acquired by extensive observations of kids' learning activities and learning environments, as well as through focus group discussions (FGD) involving school principals, instructors, and parents. Results: The qualitative analysis of the data revealed that the inclusion of human values derived from the local culture is a pertinent pedagogical approach within the independent learning curriculum. Conclusions: The efficacy of this strategy in enhancing the holistic development of Pancasila pupils has been well-documented.